Knowledge, attitude, and practices of adolescents and peer educators in relation to the components of the National Adolescent Health Program in India: findings from a cross-sectional survey - Nayak, Gayatri; Bahl, Deepika; Bassi, Shalini; Maity, Heeya; Mason-Jones, Amanda J.; Arora, Monika; Dutta, Ambarish (Frontiers in Public Health, 2024)
Background Adolescence is a critical period of growth and development. Many adverse health outcomes in adulthood begin during adolescence, often due to insufficient knowledge and attitudes resulting from a lack of education. Therefore, appropriate knowledge, attitudes, and practices (KAP) regarding various aspects of health are essential for holistic adolescent and lifelong health. In India, the Rashtriya Kishore Swasthya Karyakram (RKSK or National Adolescent Health Strategy) has utilized an innovative peer-education approach to engage with adolescents and improve their KAPs. Amid limited evidence, we aimed to assess the KAP of adolescents regarding the six themes of the RKSK, with a particular focus on the status of peer educators (PEs). Our objective was to evaluate these aspects disaggregated by sex and to examine how engagement with the RKSK peer-education program influenced their KAP. Methods A cross-sectional survey of 238 peer educators and 2885 adolescents enrolled under peer educators was conducted in two localities; Madhya Pradesh and Maharashtra states. KAPs were estimated using descriptive statistics then disaggregated by gender. Practice scores of nutrition and non-communicable disease (NCD) were modelled upon engagement with RKSK (graded as 0, 1, 2, 3). Results Knowledge was highest regarding substance misuse and lowest in the domains of sexual and reproductive health, and violence and injury. PEs possessed greater knowledge in most domains as compared to adolescents enrolled under them. Attitudes toward abstention from substance misuse were positive, whereas attitudes toward injury and violence, and sexual health, were suboptimal. Boys exhibited better practices related to NCDs, while their nutritional practices were comparatively worse than girls. The RKSK engagement was associated with better nutritional practices: adjusted relative risks (RRs) being 1.04 (95% confidence interval [CI]: 0.94–1.15), 1.12 (1.04–1.21), and 1.21 (1.13–1.31), respectively, for engagement scores 1, 2, and 3 with reference to score 0. The relationship between RKSK engagement and NCD-related practices was restricted to the top engagement group. Conclusion The knowledge regarding sexual health, and injury and violence, was grossly deficient in adolescents. These components must be prioritized in the program because they are critical for health not only across the life course of individuals but also across generations. However, the RKSK engagement was associated with better practices in a variety of domains, which should be leveraged in the future.